Musicogenic epilepsy: Expanding the spectrum of glutamic acid decarboxylase 65 neurological autoimmunity. (25th March 2021) - Smith, Kelsey M.; Zalewski, Nicholas L.; Budhram, Adrian; Britton, Jeffrey W.; So, Elson; Cascino, Gregory D.; Ritaccio, Anthony L.; McKeon, Andrew; Pittock, Sean J.; Dubey, Divyanshu
Abstract: The objective of this study was to describe serological association of musicogenic epilepsy and to evaluate clinical features and outcomes of seropositive cases. Through retrospective chart review, musicogenic epilepsy patients were identified. Among 16 musicogenic epilepsy patients, nine underwent autoantibody evaluations and all had high‐titer glutamic acid decarboxylase 65–immunoglobulin G (GAD65‐IgG; >20 nmol·L –1, serum, normal ≤ .02 nmol·L –1, eight women). Median GAD65‐IgG serum titer was 294 nmol·L –1 (20.3–3005 nmol·L –1 ), and median cerebrospinal fluid titer ( n  = 4) was 14.7 nmol·L –1 . All patients had temporal lobe epilepsy, and bitemporal epileptiform abnormalities were common. Right temporal lobe seizures were most frequently captured when seizures were induced by music on electroencephalogram (3/4; 75%). Intravenous (IV) methylprednisolone and/or IV Ig (IVIG) was utilized in four patients, with one having greater than 50% reduction. Rituximab ( n  = 2) and mycophenolate ( n  = 1) were ineffective. Two patients underwent right temporal lobe resections but continued to have seizures. Vagus nerve stimulation was effective at reducing seizures in one patient by 50%, and an additional patient was seizure‐free by avoiding provoking music. Right temporal lobe epilepsy was more common among patients with musicogenic epilepsy when compared to nonmusicogenic GAD65 epilepsies ( n  = 71, 89% vs. 47%, p  = .03). GAD65‐IgG should be tested in patients with musicogenic epilepsy, given implications for management and screening for comorbid autoimmune conditions.